Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1177/0907568206062943
|View full text |Cite
|
Sign up to set email alerts
|

The Varying Vulnerability of African Orphans

Abstract: This article is based on a qualitative study carried out in Lira District, northern Uganda, to assess the situation of orphans cared for in extended families. The objective of the article is to bring attention to the varying vulnerability of different categories of orphans. The methods employed in data collection included ethnographic fieldwork, qualitative interviews and focus group discussions. The study found that the decision-making process that leads particular orphans to particular homes, the kin categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…7 This is a potential impact hypothesized by Foster and Williamson (2000) in their literature review, although they cite no studies which examine this issue. This is also the trend observed by Oleke et al (2006) in their study of determinants of orphans' wellbeing. However, they find that early marriage among female orphans is explained by the desire of the women themselves, rather than financial or other pressure from their households.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…7 This is a potential impact hypothesized by Foster and Williamson (2000) in their literature review, although they cite no studies which examine this issue. This is also the trend observed by Oleke et al (2006) in their study of determinants of orphans' wellbeing. However, they find that early marriage among female orphans is explained by the desire of the women themselves, rather than financial or other pressure from their households.…”
Section: Introductionsupporting
confidence: 80%
“…6 High mortality rates in theory would suggest earlier marriage but for HIV specifically, it may not if the disease is linked with marriage. Oleke et al (2006) also report that respondents identified early marriage as a means of preventing infection.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study attributed the young age at sexual debut in South Africa to the apparent tolerance of premarital sex (Pillow, 2004). The rapidly changing family structure, that is now characterized by single parent households, extended and child headed families, encourages early age at sexual debut as a survival strategy against the stresses of poverty, subsequently leading to pregnancy (Oleke, et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…By age 19, only 12% of girls are still in school [15]. Younger female OVC aged between 5 and 12 years are at a greater risk of missing out on education as they are in demand as domestic servants for families with young children in urban centres; whereas older female OVC tend to drop out of school and marry early, sometimes as early as the age of 15 years [10]. OVC are more likely to have received no secondary school education and to have started sex early and married, which, in turn were associated with poor reproductive health [1].…”
Section: School Dropout Early and Forced Marriagesmentioning
confidence: 99%
“…Whereas up to 96% of all children in Uganda have some level of vulnerability, it is 51% (totaling 8 million) who have been classified according to varying degrees of vulnerability. One out of every four households in Uganda has at least one orphan or vulnerable child [10] [11].…”
Section: Introductionmentioning
confidence: 99%